Chemical Compound, Phytochemical and Toxicity on Green Rough-backed Puffer from Cirebon District - Ginanjar Pratama; - - Nurjanah; Ruddy Suwandi; Agoes Mardiono Jacoeb (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
This aims of study was to assess yield, nutrient content and in vitro assay of extract on green rough-backed puffer from Cirebon district. The method used in this study was the proximate analysis, phytochemicals, and BSLT test of extracts on three parts of puffer fish (meat, viscera and skin). Puffer fish used measure around 10-13 cm. The yield obtained was meat 37.80%, bone 45.71%, viscera 7.25% and skin 9.23%. Protein content showed greatest potential, protein in the fish meat was 18.54% while the skin was 25.31%. Phytochemical test showed the entire extract has a positive value for alkaloids and have a negative value on the other reagents, except meat extract on molisch test. Phytochemical test results indicated that the meat of green rough-backed puffer contain tetrodotoxin, but the amount was unknown. LC50 values in meat extract was 104.3498μg/mL, extract the viscera of 105.4564μg/mL, and the skin extract was 104.9637μg/mL. These results showed that the extract of meat, viscera and skin of the puffer fish is not toxic, although there are indications of tetrodotoxin in the flesh.Keywords: extracts, phytochemical, green rough-backed puffer, nutrient content